Neglected cleft lip Teisser Type 4 deformity: Anesthesiologist concerns (Indian Journal of Case Reports, 2025)
Since craniofacial anomalies are one of the most common causes of predicted difficult airway, they present a problem to anesthesiologists. To prevent serious issues, it is important to anticipate and prepare for difficult airway management beforehand. Developing a safe anesthetic plan requires an understanding of the development, features, and unique anesthetic problems of the more prevalent anomalies. The successful airway care of a Tessier No. 4 anomalous infant with cleft lip, cleft palate, and left orofacial cleft is described.